SICILIAN JURASSIC PHYSIOGRAPHY AND GEOLOGIC REALMS (ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Two tectono-sedimentary domains, which were deformed during the Neogene and evolved into two large structural sectors, characterize the Sicilian Jurassic: the Maghrebides and Peloritani. Africa margin sediments, passing downward to Triassic successions and perhaps originally to Paleozoic deposits, characterize the former. The latter belongs to the European "Calabrian Arc", where the Jurassic transgressively rests on a continental substrate (i.e. the crystalline Variscan basement). These domains are characterized by four sedimentary facies: shallow platform-derived limestones; condensed seamount-type red limestones; nodular limestones with ammonites; deep radiolarites and shales. These facies are illustrated in a dozen of stratigraphic logs. The drowning of most Triassic-Liassic carbonate platforms or ramps and the deepening of adjacent basins came with inferred Jurassic strike-slip tectonics, connected to the relative movement of Africa (Gondwanan part) vs Europe (Laurasian part); the same strike-slip tectonics may have caused scattered intraplate volcanic seamounts found in Maghrebides. During the Jurassic the Maghrebide realm was characterized by the interfingering of basins and carbonate platforms. During the Early and Middle Liassic, carbonate platforms and ramps were dominant. Since Toarcian either radiolarites in some basins or Ammonite-bearing calcareous muds developed with intervening basaltic flows, and were accompanied by condensed pelagic carbonates on the ensialic seamount-type highs. The Peloritani realm displays similar characteristics, but with later transgression on the basement, several strike-slip basins and without any volcanoes.